Implementation and development of guidelines in the emergency services in Kosovo – PARIHS framework. (13th November 2019) - Hodza-Beganovic, R; Carlsson, H; Lidberg, H; Blaku, V; Berggren, P
Abstract: Background: The aim of this project is to create understanding on the determinant factors enhancing adherence to treatment guidelines for the emergency medical services in Kosovo (EMSK). Focus is on barriers, and enablers while introducing the guidelines. It is aiming to create clearance and understanding of how and why the implementation outcomes are achieved. The factors influencing implementation will be mapped in three main domains. The domains are part of the determinant framework Promoting Action on Research Implementation in Health Services (PARIHS). Each of the domains is further divided into sub-constructs. Methods: The process of implementing treatment guidelines into the emergency medical services in Kosovo was observed and documented by 4 researchers, using a participatory research design. The PARIHS framework that consists of three core components: evidence, context, and facilitation was applied to make clarity on what works better and why, in order to achieve the outcomes of the implemented guidelines. Results: The preliminary results have shown that the three constructs have an important role in the process of implementation. The domain evidence determined the way the evidence based practice is conceived in this particular setting. The domain context concerns the organization and teamwork shaped challenges and possibilities for adherence to the guidelines. The role of an external facilitator was of specific importance. Conclusions: The PARIHS framework serves in both practical and theoretical planning of an intervention. In the present project it provides clarity on planning of the process, while also offer understanding of the elements that contribute to the sustainability of the intervention. Finally the lessons from the approach can be replicated in similar context. Key messages: Implementation projects can be more successful suing a framework to direct the effort. Such interventions should be premised with clarity on the evidence, the local context, and facilitation factors.